قاعدة لا ضرر ولا ضرار وتطبيقاتها التربوية والاجتماعية: The principle of 'No Harm and No Reciprocating Harm’ and its Educational and Social Applications - Abdulkarim Alahmed, Ahmed Abdulhakim; Jibo, Salihu Musa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تُعد تربية الناشئة من الأمور ذات الأهمية العالية التي يتحتم علينا العناية بها، فهي أساس بناء المجتمعات، وذلك لا يخفى على كل عاقل، ومن هذا المنطلق شرعت في كتابة هذا البحث الذي قد يعين على تحقيق هذا المقصود، واخترت رده إلى قاعدة فقهية عظيمة ترجع إليها غالب المسائل الشرعية، ألا وهي قاعدة لا ضرر ولا ضرار، فإن القواعد الفقهية لا غنى عنها في القضايا المستجدة، فهي تجمع الفروع الفقهية تحت أصل واحد وتسهل على العالم بها تنزيل القضايا المستجدة تحت كل أصل، فقمت بتعريف القواعد الفقهية وذكر أقسامها وبيان أهميتها من خلال المنهج الوصفي، والمنهج التحليلي، وذلك تمهيدا لموضوع البحث، ثم ذكرت بعض التطبيقات التربوية المستفادة من القاعدة استنادا إلى المنهج التطبيقي والتي أظهرت أن الأضرار الفكرية، والجسدية، والنفسية، والأخلاقية، والاجتماعية المتعلقة بالناشئة كلها يجب دفعها بشتى الوسائل الممكنة، فقاعدة لا ضرر ولا ضرار عامة تشمل كل الأضرار الواقعة والتي يمكن وقوعها، وبذلك تتبين الحاجة للرجوع إلى الدين الإسلامي، فهو المرجع الأول لحل جميع المشكلات في كل زمان ومكان. ABSTRACT Rising the younger generation is one of the most important responsibilities that we must take seriously, as it forms the foundation of building societies, something that is evident to every rational person. Based on this understanding, I undertook the task of writing this research paper, which I hope will contribute to achieving this vital goal. I chose to anchor the discussion in a great jurisprudential maxim that underpins most Islamic legal rulings: the principle of 'No Harm and No Reciprocating Harm' (La Darar wa La Dirar). Jurisprudential maxims are indispensable when dealing with emerging issues, as they bring together various legal branches under a unified framework, enabling scholars to apply new cases in accordance with foundational principles. In the preliminary part of this research, I defined jurisprudential maxims, outlined their categories, and highlighted their significance using both the descriptive and analytical approaches to set the stage for the main discussion. Following that, I presented several educational applications derived from this maxim, demonstrating that intellectual, physical, psychological, moral, and social harm affecting the youth must all be prevented by every possible means. The maxim 'No Harm and No Reciprocating Harm' is comprehensive, encompassing both existing and potential harms. This underscores the pressing need to return to the teachings of Islam, which remains the primary reference for solving all problems across time and place.